C4.5 ALGORITHM OPTIMIZATION WITH BACKWARD ELIMINATION SELECTION FEATURE FOR CREDITWORTHINESS ASSESSMENT - Untung Rohwadi; Amrin; Rudianto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Credit is now a trend in society. Credit problems are the history of incorrect use of credit cards. The impact can cause bad credit. If customers do not pay the debt that has been agreed with the bank, they can increase their credit risk. In this study, researchers applied the C4.5 algorithm without optimization and the C4.5 Algorithm with Backward Elimination Feature Selection Optimization to classify creditworthiness status. Researchers used 481 vehicle credit records with